Sistem Pengendalian Persediaan Bahan Bakar Minyak Solar dengan Simulasi Monte Carlo - M Hudori (Politeknik Kelapa Sawit Citra Widya Edukasi, 2014)
Inventories of high speed diesel used in palm oil plantation company as fuel of diesel equipment, such as automobile, heavy equipment, generator and other supplies is one fast moving, because their need are daily need. Therefore, supplies of high speed diesel should be considered carefully so as not to cause a high accumulation of asset and does not cause a shortage of inventory which will have an impact on the productivity of the company, particularly the productivity of the equipments.In this inventory control system, sometimes companies have problems of uncertainty, namely the uncertainty of the amount of the need and uncertainty of the order of arrival time. The condition is called probabilistic condition, where everything happen according to the probability. The condition can not be solved with the system used in the deterministic problem. It required another approach. One is by using a Monte Carlo simulation model.From the simulation results as much as 61 times, from June 1st, 2013 to July 31st, 2013 obtained frequency of order are 6 times. While the lead time that happened just 2 days, 4 days and 6 days. The daily requirement ranges from 158 liters to 860 liters. The minimum of ending inventory is 1,450 liters and the maximum is 8,180 liters. Thus never in short supply during the period. Similarly, over stock also never happened because it was never done a double order for the duration of waiting for order.